OPTIMIZATION OF HEALTHCARE FOR CHILDREN WITH RHEUMATIC DISEASES IN EPOCH OF TREATMENT WITH GENETICALLY ENGINEERED BIOLOGICAL AGENTS (BY THE EXAMPLE OF THE REPUBLIC OF BASHKORTOSTAN) - G. A. Shebaev; R. M. Shakirova; V. A. Malievskii; R. Z. Akhmetshin ("Paediatrician" Publishers LLC, 2013)
Juvenile arthritis - is the most common chronic rheumatic disorder among children, which causes rapid development of disability, decrease of the quality of life, social and psychological dysadaptation. In the majority of cases the main pathogenetic treatment is methotrexate, however when there is resistance or intolerability of this drug, therapy with genetically engineered biological agents is indicated. Aim: to develop measures of optimization of medical support for children with juvenile arthritis according to analysis of its medical and social as well as economic consequences at regional level. Patients and methods: the epidemiologic study included screening questionnaires of 43 907 children with subsequent examination of those of them with inflammatory swelling of the joints during 1 year. Formation of regional registry of children with juvenile arthritis has been performed in the Republic of Bashkortostan since 2003, regional component of the federal on-line registry has been functioning since 2011. The prevalence of juvenile arthritis, its social and economic consequences and the «costs of the disease» were established. In total there were registered 474 patients with juvenile arthritis, among them 62 receive treatment with genetically engineered biological agents. Results: an order of providing the children with juvenile arthritis with medical agents is established - in-patient treatment is performed within the framework of specialized (including high-tech) medical care; genetically engineered biological drugs for out-patient therapy are purchased at the expense of republican state resources in the network of the social support of certain population groups («regional benefit»).